Constraints Faced by the Beneficiaries of Citrus Estates in Citrus Cultivation - Singh, Gurvinder; Bhalla, JS; Rampal, VK (Indian Journal of Extension Education, 2021)
Citrus is a non-traditional crop in Punjab state, hence, it became evident to promote citrus crop and to give knowledge to the farmers about the most up-to-date techniques of citrus planting, management, harvesting, and marketing of this crop. Therefore, the Punjab Government through the State Department of Horticulture established five Citrus Estates in the natural citrus growing area of the Punjab during 2007. The study to identify the constraints faced by the beneficiaries of citrus estates in citrus cultivation in Punjab sampled 200 beneficiaries through a stratified multistage random sampling design. The average operational land holding of all respondentÂ beneficiaries was 10 acres. The technical constraints got first rank followed by storage & marketing constraints with average mean score 2.271 and 2.244. Under different five areas, susceptibility towards disease & insect pest, unfavourable weather conditions, seasonal glut in market, lack of preservation industry in the are,a and lack of mechanization in citrus processing were the major constraints.